Praktik Kerja Adil dan Keseimbangan Pekerjaan-Hidup di Industri Berkekuatan Tinggi - Yohan Purnawan; Yeni Trisna Purba; Peronika Sari BR Tarigan (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
This study aims to examine the implementation of fair work practices and work-life balance among employees in high-intensity industries in Indonesia, and their effects on organizational outcomes, including job satisfaction, organizational commitment, and performance. Fair work practices are measured across four organizational justice dimensions: distributive, procedural, interactional, and informational justice. Work-life balance is assessed through time balance, involvement balance, and satisfaction balance, guided by boundary management theory. Using a quantitative correlational design, the study collected data from 300 professional employees working in technology, finance, consulting, and startup companies across Jakarta, Bandung, Surabaya, and Bali. Data were gathered via online questionnaires and enriched through semi-structured interviews, HR manager focus group discussions, and document analysis. Data analysis involved CFA, reliability testing, Pearson correlation, and Structural Equation Modeling (SEM), including mediation tests using bootstrapping. The results indicate that fair work practices have a positive and significant effect on work-life balance (β = 0.48; p < 0.001). Additionally, both fair work practices and work-life balance positively and significantly influence job satisfaction, organizational commitment, and performance. Work-life balance also significantly mediates the relationship between fair work practices and all organizational outcomes, with significant indirect effects. Overall, the findings highlight the importance of fair workplace policies to enhance employee well-being while supporting organizational performance in high-intensity work environments.